Enzymatic enhancing of triplet–triplet annihilation upconversion by breaking oxygen quenching for background-free biological sensing - Huang, Ling; Le, Timmy; Huang, Kai; Han, Gang (Nature communications, 2021)
Triplet-triplet annihilation upconversion nanoparticles have attracted considerable interest due to their promises in organic chemistry, solar energy harvesting and several biological applications. However, triplet-triplet annihilation upconversion in aqueous solutions is challenging due to sensitivity to oxygen, hindering its biological applications under ambient atmosphere. Herein, we report a simple enzymatic strategy to overcome oxygen-induced triplet-triplet annihilation upconversion quenching. This strategy stems from a glucose oxidase catalyzed glucose oxidation reaction, which enables rapid oxygen depletion to turn on upconversion in the aqueous solution. Furthermore, self-standing upconversion biological sensors of such nanoparticles are developed to detect glucose and measure the activity of enzymes related to glucose metabolism in a highly specific, sensitive and background-free manner. This study not only overcomes the key roadblock for applications of triplet-triplet annihilation upconversion nanoparticles in aqueous solutions, it also establishes the proof-of-concept to develop triplet-triplet annihilation upconversion nanoparticles as background free self-standing biological sensors. Triplet-triplet annihilation upconversion (TTA-UC) nanoparticles (NPs) are a promising material for diverse applications, but TTA-UC is sensitive to oxygen, which hinders its biological utility. Here, the authors report an enzymatic method to deplete oxygen and amplify the upconversion of TTA-UCNP in aqueous solution, and develop background-free glucose and glucose metabolism enzyme sensors.